Crops and Climate Change: Plant quality declines as CO2 levels rise - Weigel, Hans-Joachim (eLife, 2014)
There is concern that crop plants are becoming less nutritious as the levels of carbon dioxide in the atmosphere increase.
Keywords: elevated CO2; zinc; iron; ionome; crop; human nutrition